The Associations Between Career Decision-Making Difficulties and Negative Emotional States. (August 2021) - Anghel, Ella; Gati, Itamar
Career decision-making difficulties are the challenges encountered by individuals before, during, or after choosing one's career. This study tested the associations between career decision-making difficulties and depression, anxiety, and stress, considering the career decision status of participants. Students in a precollege preparatory program filled out questionnaires at the beginning and near the end of the academic year ( N = 137). The correlations between career decision-making difficulties, as measured by the Career Decision-Making Difficulties, and negative emotional states measured by the Depression, Anxiety, and Stress Scales, were positive at both administrations ( r T1 = .24, r T2 = .38). Using a multivariate analysis of variance, we have found that those who became more decided had fewer career decision-making difficulties ( d = 1.26). The changes in career decision status were not associated with either depression, anxiety, or stress. However, overall negative emotions intensified among students who were still undecided at the end of the year ( d = 0.72). Implications for research and practice are discussed.